Analysis of the Role of Traffic Police Competence in Efforts to Reduce Congestion Levels on Highways - Suharlan Pasangka; Syahrir; Nurhaedah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Traffic congestion is a common problem faced by transportation modes in Indonesia, including Makassar City. This study aims to analyze the role of traffic police competence in reducing road congestion. Using a qualitative descriptive approach, data were obtained through in-depth interviews and participant observation with Makassar City Police Traffic Unit personnel and road users. The results show that traffic police competence, including technical skills, communication skills, digital technology mastery, and professionalism, significantly influences the effectiveness of traffic control. Although most personnel have adequate understanding and experience, there is variation in task implementation, particularly in mastery of technological systems and educational approaches to the public. This study concludes that competency improvement must be accompanied by continuous training, equitable distribution of resources, and cross-sectoral institutional synergy to achieve more efficient traffic management.